The Effect of Moringa oleifera Extract on Histopathological of Mice Testes Exposed by Monosodium Glutamate - Handoyo, Regenio Akira; Saraswati, Indah; Mochtar, Arufiadi Anityo; Armalina, Desy; Miranti, Ika Pawitra (Jurnal Kedokteran Diponegoro (Diponegoro Medical Journal), 2023)
Background: Monosodium glutamate (MSG) consumption in excess can have an impact on a man's fertility and lead to infertility. MSG has the potential to produce free radicals, which can harm cells. Antioxidants can fight off free radicals. Exogenous antioxidants are required to maintain equilibrium since there will be an imbalance if the body produces more free radicals than endogenous antioxidants. Exogenous antioxidants flavonoids are present in the leaves of the Moringa plant (Moringa oleifera L). It is thought that flavonoids have 4-5 times more antioxidant potential than vitamins. Objectives: To evaluate how moringa leaf extract affects the histopathological profile of MSG-exposed mouse testes. Methods: Only the posttest was used as a control group in this study. 25 male mice were used as the sample, and they were split up into five groups. The treatment group 1 (P1) received 6 g/day of MSG exposure + 300 mg/kg BW/day of moringa leaf extract, the treatment group 2 (P2) received 6 g/day of MSG exposure + 600 mg/kg BW/day of moringa leaf extract, and the treatment group 3 (P3) received 6 g/day of MSG exposure + 1200 mg/kg BW/day of moringa leaf extract. The control group (K-) received only standard feed. The mice were put to death after 30 days. The testes were removed for histological examination using hematoxylin-eosin staining, and the Johnsen scoring criteria were applied to their evaluation. Results: The data were not significant according to the Shapiro-Wilk test in the P3 group (MSG 6 g/day + Moringa Extract 1200 mg/kg BW/day). The Kruskal-Wallis test revealed that there was no significant difference between the seminiferous tubules according to the treatment group (p = 0.117). Conclusion: Moringa oleifera leaf extract protects the histopathological picture of the testes of male mice compared to the group given monosodium glutamate.